(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
Recently, a number of research groups have paid much attention to the study of Floating Offshore Wind Turbines (FOWTs). Similar to other offshore structures, the FOWTs are subjected to irregular waves and wind loads which cause a dynamic response in the structures. Under marine environmental conditions, they face many forces which prevent them from floating in the upright condition; they incline as a result of the winds, strong currents, typhoons, cyclones, storms etc. The motion of the FOWT might be changed by a change in gyroscopic effect which depends on the angular velocity and moment of inertia of the blade. Therefore, to investigate the effect of the gyro moment on the motion of the FOWT, two types of experiment were carried out in a water tank using a 1/360 scale model of a prototype FOWT. Firstly, the interaction between the rotary motion of the wind turbine blade and the dynamic motion of the SPAR-type FOWT was studied at small angles of inclination in regular waves. Secondly, the interaction between the change of rotational speed as well as moment of inertia of the blade and the motion of the FOWT was studied. In this paper, numerical calculations have been carried out using potential theory based on the 3D panel method. Finally, the experimental results are compared with the results of numerical simulation and findings are discussed. DOI: http://dx.doi.org/10.3329/jname.v9i1.10732 Journal of Naval Architecture and Marine Engineering 9(2012) 67-79